Peran Kepala Sekolah dalam Optimalisasi Modal Sosial dan Budaya Daerah sebagai Sumber Daya Alternatif dalam Pengembangan Pendidikan Islam di Sekolah Dasar - Isti Maimunah; Muchammad Eka Mahmud; Ahmad Muaddin (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2026)
Islamic education in elementary schools plays a strategic role in shaping the character, morals, and social identity of students, but still faces limited facilities, low integration of contextual values, and the dominance of cognitive learning. This study aims to analyze the optimization of regional social and cultural capital as an alternative resource in the development of Islamic education at SDN 018 Palaran, including the role of the principal, its implementation, and its impact on strengthening Islamic education based on local wisdom. The research method used is a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The results show that the principal plays a role as a transformational leader, motivator, and mediator in optimizing regional social and cultural capital by strengthening school-community cooperation. The application of social capital is seen in increased community participation in religious activities, while local culture is integrated into the learning and habituation of religious values ​​at school. The impacts include strengthening students' religious character, increasing community participation, creating a conducive school environment, and strengthening students' cultural and Islamic identities. Thus, regional social and cultural capital has proven to be an effective alternative resource in developing contextual, participatory, and sustainable Islamic education at SDN 018 Palaran.